Interfaces gestuais baseados no controlador Leap Motion - Bizarro, João Pedro Pereira (2021)
Submitted by Elsa Lemos (elsa@isec.pt) on 2020-03-11T14:39:39Z No. of bitstreams: 1 Joao-Pedro-Pereira-Bizarro.pdf: 2992440 bytes, checksum: d39ceed576ac37b2e03223370618adc1 (MD5)